2022
DOI: 10.1038/s41467-022-28369-7
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal-epithelial crosstalk shapes intestinal regionalisation via Wnt and Shh signalling

Abstract: Organs are anatomically compartmentalised to cater for specialised functions. In the small intestine (SI), regionalisation enables sequential processing of food and nutrient absorption. While several studies indicate the critical importance of non-epithelial cells during development and homeostasis, the extent to which these cells contribute to regionalisation during morphogenesis remains unexplored. Here, we identify a mesenchymal-epithelial crosstalk that shapes the developing SI during late morphogenesis. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 58 publications
1
35
0
Order By: Relevance
“…The reciprocal inhibition between the Hh and Wnt signaling pathways the balance between cell proliferation and differentiation (Ding & Wang, 2017;Herman et al, 2018). Pharmacological research has revealed the integration between Hh and Wnt signaling through active and inhibitory drugs (Maimets et al, 2022). The Hh pathway acts upstream of Wnt to inhibit Wnt signaling activation; However, Wnt activation may salvage suppressive Hh signaling in regulating amphibian and chick limb regeneration (Moura et al, 2014;Mescher, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The reciprocal inhibition between the Hh and Wnt signaling pathways the balance between cell proliferation and differentiation (Ding & Wang, 2017;Herman et al, 2018). Pharmacological research has revealed the integration between Hh and Wnt signaling through active and inhibitory drugs (Maimets et al, 2022). The Hh pathway acts upstream of Wnt to inhibit Wnt signaling activation; However, Wnt activation may salvage suppressive Hh signaling in regulating amphibian and chick limb regeneration (Moura et al, 2014;Mescher, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…However, as suggested by some previous studies, bulk RNA‐seq is an effective strategy and could identify the most significant hub genes and key pathways, giving clues for later research (Jia et al., 2017; Ozturk et al., 2013). In addition, since there are some pathways involved interactions between epithelium and mesenchyme such as SHH or WNT (Maimets et al., 2022; Sarkar et al., 2000), sequencing for the mixture tissue will not conceal the possible interactions involving the two different tissues. In the future, some new techniques such as high‐precision micromanipulation or single‐cell sequencing could be applied to give us more precious and insightful evidence.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo adult tissue processing for RNA-seq Crypts were isolated from the proximal 20% of the small intestine and processed to obtain single cells as previously described in three biological replicates (10). Briefly, whole epithelium samples were isolated from the proximal 20% of the small intestine using EDTA solution and incubated with collagenase to obtain single-cell suspensions.…”
Section: Boundary Analysismentioning
confidence: 99%
“…Following villus formation, equipotent epithelial progenitors give rise to functionally defined adult stem cells (3,4), which, following birth, become confined to the bottom of the intestinal crypts and are responsible for replenishment of the epithelium throughout life (5). Although the histological and morphological changes during this transition from the fetal to the adult intestine have been extensively described (4,(6)(7)(8)(9)(10), how the process is orchestrated at the molecular level remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%